Maternally transmitted non-bacterial male killer in Drosophila biauraria. (11th October 2017) - Kageyama, Daisuke; Yoshimura, Kanamu; Sugimoto, Takafumi N.; Katoh, Takehiro K.; Watada, Masayoshi
Abstract : A maternally inherited, all-female trait is widely found among arthropods, which is caused by bacterial endosymbionts such as Wolbachia, Rickettsia, Spiroplasma and Cardinium . We discovered a single female of Drosophila biauraria, collected from Tomakomai, Hokkaido, Japan, that produced all-female offspring. This all-female trait was maternally inherited in the iso-female line (SP12F) by backcrossing with males of a normal line (SP11-20) with a 1 : 1 sex ratio derived from the same population. The all-female trait was not affected by tetracycline treatment performed for two consecutive generations. However, the microinjection of filter-sterilized homogenate of SP12F females into SP11-20 females established all-female matrilines. Our data suggest the role of transmissible agents, most likely viruses, but not bacteria or protists, as the possible cause of the all-female phenotype, which is likely to be achieved by killing of male embryos because egg hatch rates of SP12F were nearly half those of SP11-20. This is the first report in Diptera to demonstrate a maternally inherited virus-like element as the cause of the male-killing phenotype in D. biauraria .